The Impact and Influence of Four Agents of Atheistic Anthropocentrism on Society and the Environment, in the Light of Laudato Si’ - Richard Pavlić; Bruno Rukavina (Diacovensia)
The paper deals with the impact and influence of atheistic anthropocentrism on society and the environment. This impact is conducted through agents of atheistic anthropocentrism or social deviations: relativism, hedonism, consumerism, and materialism. The authors have researched conceptual analysis of anthropocentrism and social deviations, which they called four agents of atheistic anthropocentrism. That research opened several new questions that should be further analyzed. One of those questions was about the impact and influence of four agents of atheistic anthropocentrism on society and the environment. The main goal of the paper is to present dangers and deviations that emerge from atheistic anthropocentrism while also taking into account the contribution of Pope Francis and the guidelines and warnings he gives in the encyclical Laudato Si'.